Epidemiology of Eye Diseases in a Community Eye Camp in Northern Pakistan: Doi: 10.36351/pjo.v41i4.2192 - Shahid, Erum; Shahzaib, Muhammad; Fasih, Uzma; Jafri, Asad raza (Pakistan Journal of Ophthalmology, 2025)
Purpose: To determine the epidemiology of eye diseases in Skardu, Gilgit-Baltistan, in the North of Pakistan. Study Design: Cross sectional observational study. Place and Duration of Study: Camp organized by a Private Eye Hospital in Skardu, Gilgit Baltistan from 22nd April to 28thApril 2024. Methods: In this 7-day camp, outreach services were provided in Dambudas, Khaplu, and Shigar, offering routine eye examinations, treatment for minor ocular problems, and spectacles for refractive errors, while surgical cases were referred to the main hospital. Comprehensive evaluations included slit-lamp examination, visual acuity testing, fundoscopy, tonometry for glaucoma suspects, and refraction. Medicines were dispensed free, and cataract patients were counseled and scheduled for surgery. Frequencies are computed for categorical variables and means for numerical data. Results: There were 3411 patients with mean age of 36.48±11.34 years. Males accounted for 57% of the patients. The highest percentage of patients was 61 years and above (26.53%). There were 65.79%patients with anterior segment diseases. Allergic conjunctivitis was seen in33.56%, and pterygium in 1.32% of individuals. Diabetic retinopathy was seen in 1.73%, cataracts in 7.33%, and glaucoma in 1.91%. Refractive errors were reported in 30.35% with hypermetropia (15.48%) being the most common. Medicines were prescribed to 62.22%, spectacle prescriptions to 24.89%, and surgical interventions were performed in 3.98% of patients. Conclusion: The allergic conjunctivitis was most frequent ocular problem, followed by refractive errors (hypermetropia being the commonest). Diabetic retinopathy was the most common disease among posterior segment pathology.